INFECTIOUS MONONUCLEOSIS: CLINICAL AND LABORATORY FEATURES IN CHILDREN OF THE SAMARKAND REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Infectious mononucleosis (IM) is a clinically significant viral infection caused predominantly by the Epstein–Barr virus (EBV), a member of the Herpesviridae family. Approximately 80–90% of the global population acquires EBV infection during their lifetime. Early and accurate identification of infectious mononucleosis contributes to improved treatment outcomes, especially through reducing the duration of fever, lowering lymphoid tissue proliferation, and accelerating the resolution of hepatocellular cytolysis.